HUBUNGAN TINGKAT KECERDASAN EMOSIONAL DAN INTELEKTUAL DENGAN KEBERHASILAN BELAJAR - Sulaiman Effendi (E-Jurnal Aksioma Ad-Diniyyah : The Indonesian Journal of Islamic Studies, 2013)
The purpose of research is to analyze the correlation between emotional intelligence and intellectual learning success. Correlational study was conducted on the students of Madrasah Aliyah Manahijussadat Cibadak, which consists of 37 people and hypothesis testing is done using correlation analysis. The results indicate that there is a positive relationship and intellectual level of emotional intelligence with learning success.